The Equity Premium in Brazil - Biehl, Carlos Augusto (2008)
This dissertation studies on one of the most famous puzzles in finance, the equity premium puzzle. The Equity Premium Puzzle has been studied repetitively in the financial literature since 1985, year of the publication of the of Mehra and Prescott work. The abundant number of studies and different explanations for the puzzle are revised as many theories have been offered to explain the equity premium puzzle. The purpose of this dissertation is to analyze and valuate the existence of the Equity Premium in Brazil during the period from 1974 up to 2007. The Brazilian literature was revised and according to it, the existence of the Equity Premium Puzzle still under controversy.